A lightweight, high temperature resistant silicon carbide aerogel and a preparation method thereof
By introducing nanowire-filled layered structures into silicon carbide aerogels, combining the pre-reduction of graphene oxide and high-temperature gas-phase silicone penetration process, the shortcomings in the existing silicon carbide aerogels in thermal insulation and mechanical properties are solved, and the preparation of high-performance multifunctional materials is realized.
Patent Information
- Application Number
- CN202410744401.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-06-11
AI Technical Summary
The existing silicon carbide aerogels have shortcomings in thermal insulation and mechanical properties, and the preparation process is complex and costly, making it difficult to meet the needs of high-performance multifunctional materials.
By mixing graphene oxide powder with ascorbic acid and deionized water, pre-reduction, freeze-drying and high-temperature thermal reduction, a layered reduced graphene oxide aerogel was obtained, and then mixed with silicon powder and silica powder for high-temperature vapor-permeable silicon to prepare nanowire-filled layered structure silicon carbide aerogel.
Silicon carbide aerogels that achieve ultra-light, high mechanical properties, ultra-high temperature insulation (infrared stealth) and fire resistance have good fatigue resistance and high temperature stability, and are suitable for aerospace, ships and steam turbines and other fields.
Smart Images

Figure CN118580088B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, and in particular to a lightweight, high-temperature resistant silicon carbide aerogel and a preparation method thereof. Background Art
[0002] Aerogel is an ultra-light and highly porous material due to its unique three-dimensional structure, mainly including oxide aerogel, polyimide aerogel, carbon aerogel, ceramic aerogel, etc. As a typical ceramic aerogel, silicon carbide aerogel has the advantages of high temperature resistance, stable physical and chemical properties, and low thermal expansion coefficient. It is an excellent ultra-high temperature thermal protection material.
[0003] However, the thermal insulation and mechanical properties of silicon carbide aerogels need to be further strengthened. The microstructure regulation of materials is one of the important means to improve the performance of silicon carbide aerogels. At present, many scholars have found that the thermal and mechanical properties of materials can be effectively improved by preparing layered aerogels. However, how to further improve its structure is a key topic. At the same time, the preparation of nanowire aerogels is also an effective method to improve the thermodynamic properties of silicon carbide aerogels. How to regulate the microstructure of silicon carbide nanowire aerogels and layered silicon carbide aerogels to achieve a synergistic improvement in their thermal and mechanical properties is a key issue. At the same time, on the basis of microstructure regulation, how to simplify the process and reduce costs is an urgent problem to be solved. In addition, with the development of science and technology, various fields have put forward higher requirements on the strength, temperature resistance, lightness, thermal insulation, and fire resistance of aerogel thermal insulation materials.
[0004] In summary, it is of great significance to study a high-performance and multifunctional silicon carbide aerogel with a new structure. Summary of the invention
[0005] The purpose of the present invention is to provide a lightweight, high-temperature resistant silicon carbide aerogel and a preparation method thereof, which can prepare nanowire-filled layered silicon carbide aerogel having ultra-lightness, high mechanical properties, ultra-high temperature thermal insulation (infrared stealth) properties and fire resistance.
[0006] A first aspect of the present invention provides a method for preparing a lightweight, high temperature resistant silicon carbide aerogel, comprising the following steps:
[0007] S1, mixing and dispersing graphene oxide powder, ascorbic acid and deionized water, and then pre-reducing them to obtain pre-reduced graphene oxide gel;
[0008] S2, freezing the pre-reduced graphene oxide gel, and then freeze-drying and high-temperature thermal reduction after the pre-reduced graphene oxide gel is completely frozen to obtain a layered reduced graphene oxide aerogel;
[0009] S3. Mixing a mixed powder of silicon powder and silicon dioxide powder as a silicon source with layered reduced graphene oxide aerogel, and performing high-temperature gas phase siliconization to obtain nanowire-filled layered silicon carbide aerogel.
[0010] Preferably, step S1 comprises:
[0011] S11, dissolving graphene oxide powder in deionized water to obtain a graphene oxide solution;
[0012] S12, adding ascorbic acid to the graphene oxide solution, performing ultrasonic dispersion and stirring to obtain a mixed solution;
[0013] Preferably, the frequency of ultrasonic treatment is 30-80 KHz, the ultrasonic treatment time is 0.5-1 h, the ultrasonic treatment and stirring temperature is 10-20 ° C, and the stirring time is 1-2 h;
[0014] S13, pouring the mixed solution into a mold, placing the mold in an oven at 60-70° C. for 1-2 hours for pre-reduction, and obtaining a pre-reduced graphene oxide gel.
[0015] Preferably, the bottom of the mold has a polydimethylsiloxane (PDMS) wedge block, and the wedge angle of the wedge block is not less than 20°, preferably 20°.
[0016] Preferably, the mold is a plastic mold.
[0017] Preferably, the concentration of the graphene oxide solution is 5 to 20 mg / ml, more preferably 10 mg / ml.
[0018] Preferably, the mass ratio of the graphene oxide powder to ascorbic acid is 1:(1.5-2.5), more preferably 1:2.
[0019] Preferably, step S2 comprises:
[0020] S21, after the pre-reduction is completed, the mold is placed on a copper block that has been immersed in liquid nitrogen in advance until it is completely frozen;
[0021] S22, after complete freezing, placing the mold into a pre-frozen freeze dryer for drying for 70 to 80 hours, controlling the temperature at -50°C to -70°C and the pressure at 3 to 10 Pa;
[0022] Preferably, the controlled temperature is -60°C and the pressure is 5Pa;
[0023] S23, subjecting the dried aerogel to high-temperature thermal reduction carbonization in a nitrogen atmosphere at 700 to 900° C. (preferably 800° C.) for 1 to 3 hours to obtain a layered reduced graphene oxide aerogel.
[0024] Preferably, step S3 includes:
[0025] S31, fully mixing silicon powder and silicon dioxide powder, and placing the obtained mixed powder as a silicon source at the bottom of a crucible;
[0026] S32, placing the layered reduced graphene oxide aerogel on the mixed powder;
[0027] S33, placing the crucible in a tubular furnace, heating it to 1500-1600° C. (preferably 1550° C.) in an inert gas atmosphere for high-temperature gas phase siliconization to obtain nanowire-filled layered silicon carbide aerogel.
[0028] Preferably, the mass ratio of the layered reduced graphene oxide aerogel, silicon powder and silicon dioxide powder is 1:(3-4):(9-10), more preferably 1:4:9.
[0029] Preferably, the inert gas is argon.
[0030] Preferably, the heating is carried out according to a gradient heating method (the heating rate is fast at first and then slow, from 5°C / min to 1.5°C / min), and the temperature is heated to 1500-1600°C for high-temperature vapor phase siliconization, and the holding time is 2-3h.
[0031] A second aspect of the present invention provides a lightweight, high temperature resistant silicon carbide aerogel, which is prepared by the above-mentioned preparation method.
[0032] The third aspect of the present invention provides the application of the above-mentioned lightweight and high temperature resistant silicon carbide aerogel.
[0033] Specifically, the application includes:
[0034] A. Used as aerospace structural thermal protection material. In space exploration, the surface of the aircraft may be exposed to high temperature and mechanical shock. This material is lightweight, highly elastic, and resistant to high temperatures, and is expected to be used in aerospace structural thermal protection materials;
[0035] B. Used as heat insulation / stealth material in the engine of ships / aircraft and other equipment. This part requires the material to have good high temperature resistance, fire resistance and load-bearing capacity. This material has these properties. In addition, military ships and military aircraft also have certain requirements for their high temperature stealth performance. This material also has good infrared stealth performance at high temperatures;
[0036] C. Used as refractory material for steam turbine furnace. Generally, the furnace wall temperature of steam turbine is 1100-1200℃. At the same time, it has a certain load-bearing capacity. This material has good fireproof and heat-insulating properties and a certain load-bearing capacity. It is expected to be used as refractory material for furnace.
[0037] Beneficial effects:
[0038] (1) The preparation method of the present invention can not only effectively regulate the structure of reduced graphene oxide aerogel, but also use the regulated reduced graphene oxide aerogel to perform siliconization treatment to achieve structural regulation of silicon carbide aerogel and obtain nanowire-filled layered structure silicon carbide aerogel.
[0039] (2) The density of the silicon carbide aerogel prepared by the present invention is only 0.018 g / cm 3 It can achieve 100% rebound under 60% compression strain and has good fatigue resistance. At the same time, it can carry a mass more than 1800 times its own without deformation. It does not deform under ablation at a flame of about 1200°C for 1 hour. Under a heat source of about 1000°C and a sample thickness of 2cm, the back temperature is about 45°C. It has excellent ultra-lightness, high mechanical properties, ultra-high temperature thermal insulation (infrared stealth) properties and fire resistance, and has broad application prospects in the field of high-temperature thermal protection materials.
[0040] (3) The preparation method of the present invention has low cost, simple steps, easy operation, green and environmental protection, short production cycle, high controllability, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 The present invention provides a flow chart for preparing the lightweight, high temperature resistant silicon carbide aerogel.
[0043] Figure 2 The volume, mass, density and mechanical bearing capacity of the sample of Example 1 of the present invention are displayed.
[0044] Figure 3 This is a microscopic morphology of the sample of Example 1 of the present invention.
[0045] Figure 4 This is a diagram of the mechanical properties of the sample of Example 1 of the present invention.
[0046] Figure 5 This is a diagram of the thermal insulation and high-temperature infrared stealth performance testing device of the sample of Example 1 of the present invention.
[0047] Figure 6 This is a graph showing the thermal insulation and high-temperature infrared stealth performance of the sample of Example 1 of the present invention.
[0048] Figure 7 This is a fire resistance test diagram of the sample of Example 1 of the present invention.
[0049] Figure 8 This is a microscopic morphology of the sample of Example 2 of the present invention.
[0050] Fig. 9 This is an optical picture of the sample of Example 2 of the present invention.
[0051] Fig.10 This is a microscopic morphology of the sample of Example 3 of the present invention.
[0052] Fig.11 This is an optical picture of the sample of Example 3 of the present invention.
[0053] Fig.12 This is a microscopic morphology of the sample at a wedge angle of 10° in Comparative Example 1 of the present invention.
[0054] Fig.13 It is a schematic diagram of the freezing method (bidirectional) with a wedge angle of the present invention.
[0055] Fig.14 This is a microscopic morphology of the sample of Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0056] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0057] It should be noted that the terms used here are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprising", "including", "having", "containing" are used in this specification, it is indicated that there are features, steps, operations, devices, components and / or combinations thereof, which are all open terms, that is, it means including but not limited to. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the range.
[0058] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] Example 1
[0060] This embodiment provides a method for preparing a lightweight, high temperature resistant silicon carbide aerogel (silicon carbide aerogel with a layered structure filled with nanowires). The process flow chart is as follows: Figure 1 As shown, the following steps are included:
[0061] (1) Preparation of pre-reduced graphene oxide gel
[0062] First, a certain amount of graphene oxide powder was weighed and dissolved in deionized water at a concentration of 10 mg / ml; then, a certain amount of ascorbic acid was added to the graphene oxide solution, and the mass of ascorbic acid was twice the mass of graphene oxide. The mixed solution was ultrasonically dispersed for 30 minutes, stirred for 2 hours, and then poured into a plastic mold with a polydimethylsiloxane (PDMS) wedge (wedge angle of 20°) block, and pre-reduced at 60°C for 100 minutes to transform it from a sol state to a microgel state.
[0063] (2) Preparation of layered reduced graphene oxide aerogel
[0064] The mold was placed on a copper block that had been immersed in liquid nitrogen in advance. After being completely frozen, it was placed in a pre-frozen freeze dryer and dried for 72 hours at -60°C and 5 Pa. In order to remove impurities and enhance chemical cross-linking, the dried aerogel was heat treated at 800°C for 2 hours to obtain reduced graphene oxide aerogel.
[0065] (3) Preparation of nanowire-filled layered silicon carbide aerogel by vapor phase siliconization
[0066] The above aerogel is used as a carbon source, and silicon powder and silicon dioxide powder are used as silicon sources, and they are fully mixed, and the mass ratio of reduced graphene oxide aerogel to silicon powder and silicon dioxide powder is 1:4:9. The carbon source is placed on the silicon source, and they are placed together in a crucible and put into a tubular furnace. After evacuation, argon gas is filled as a protective atmosphere, and the temperature is heated to 1550°C according to the gradient heating method (the heating rate is fast at first and then slow, from 5°C / min to 1.5°C / min) for high-temperature gas phase siliconization, and the heat preservation time is 2h to obtain nanowire-filled layered structure silicon carbide aerogel.
[0067] like Figure 2As shown, this embodiment also provides a lightweight and high temperature resistant silicon carbide aerogel, wherein (a) to (d) are respectively the volume, mass, density, and mechanical bearing capacity display diagrams of the silicon carbide aerogel samples prepared in this embodiment. It can be seen from the figure that the silicon carbide aerogel prepared in this embodiment is white, has neat specifications, and has a volume of 35.9 cm 3 , mass 671.7 mg, density 18.71 mg / cm 3 , can be placed on the leaves of the green radish, and at the same time, it can bear more than 1800 times its own weight without deformation. Figure 3 It can be seen intuitively that the aerogel is composed of countless irregular nanowires and layered sheet structures (the layered sheet structures are composed of nanowhiskers), which presents a nanowire-filled layered structure. Figure 4 It can be seen intuitively that the aerogel has good resilience on different stress surfaces, which indicates that the aerogel has good mechanical impact resistance compared to other ceramic aerogels. Figure 5 The thermal insulation performance and high-temperature infrared stealth test device of the sample in this embodiment are shown in Figure 2. In order to intuitively demonstrate the ultra-high temperature infrared stealth / thermal insulation performance of the aerogel, a high-temperature thermal imager was used to take its real-time infrared thermal imaging image. Figure 6 As shown in the figure, the left side is the heating surface, showing a bright yellow-white color, while the right side is a dim purple-black color, forming a sharp contrast. At the same time, the use of software to analyze the temperature of the left and right sides shows that the temperature on the left side has been maintained at around 980°C, while the temperature on the right side has gradually increased over time. The temperature in the last 5 minutes was about 46.3°C, indicating that the aerogel has good high-temperature infrared stealth / thermal insulation properties. In order to further evaluate the high-temperature ablation resistance of the aerogel, a 60-minute ablation resistance experiment was carried out on it. The experimental temperature was about 1200°C. The results are as follows Figure 7 As shown. Figure 7 It can be seen that the external structure and shape of the aerogel did not change significantly before and after ablation, and the volume shrinkage and mass gain were both less than 1%.
[0068] The aerogel prepared in this embodiment has ultra-light density, excellent mechanical properties, excellent high-temperature stealth / thermal insulation properties, and excellent fire resistance. It is a multifunctional material with integrated functional structure. The preparation method thereof has low cost, simple steps, easy operation, green and environmental protection, short production cycle, and high controllability, and shows good application prospects in the field of ultra-high temperature thermal protection materials.
[0069] Example 2
[0070] This embodiment provides a method for preparing a lightweight layered silicon carbide nanowire aerogel, comprising the following steps:
[0071] (1) Preparation of pre-reduced graphene oxide gel
[0072] First, a certain amount of graphene oxide powder was weighed and dissolved in deionized water at a concentration of 5 mg / ml. Then, a certain amount of ascorbic acid was added to the graphene oxide solution, and the mass of ascorbic acid was twice the mass of graphene oxide. The mixed solution was ultrasonically dispersed for 30 minutes, stirred for 2 hours, poured into a plastic mold with a wedge-shaped block of polydimethylsiloxane (PDMS) (wedge angle of 20°), and reduced at 60°C for 120 minutes to transform it from a sol state to a microgel state.
[0073] (2) Preparation of reduced graphene oxide aerogel
[0074] The mold was placed on a copper block that had been immersed in liquid nitrogen in advance. After being completely frozen, it was placed in a pre-frozen freeze dryer and dried for 72 hours at -60°C and 5 Pa. In order to remove impurities and enhance chemical cross-linking, the dried aerogel was heat treated at 800°C for 2 hours to obtain reduced graphene oxide aerogel.
[0075] (3) Preparation of layered silicon carbide nanowire aerogel by vapor phase siliconization
[0076] The above aerogel is used as the carbon source, and silicon powder and silicon dioxide powder are used as the silicon source. They are fully mixed, and the mass ratio of reduced graphene oxide aerogel to silicon powder and silicon dioxide powder is 1:4:10. The carbon source is placed on the silicon source, and they are placed together in a crucible and put into a tube furnace. After vacuuming, argon gas is filled in as a protective atmosphere, and the temperature is kept at 2℃·min -1 The temperature is heated to 1600℃ at a heating rate of , and the high-temperature vapor phase siliconization is carried out, and the holding time is 2.5h.
[0077] Different from Example 1, this example can change the density and microstructure of silicon carbide aerogel by adjusting the concentration of graphene oxide, the time of pre-reduction, the ratio of carbon source to silicon source and the heat treatment process. The density of silicon carbide aerogel prepared in this example is only 9.62 mg / cm 3 The microscopic morphology and optical images of the samples are shown in Figure 8 and Fig. 9 As shown in the figure, it can be seen that the microscopic morphology of the aerogel presents a layered fiber structure; at the same time, the aerogel still has the characteristics of being lightweight and can be placed on green leaves.
[0078] Example 3
[0079] This embodiment provides a method for preparing a lightweight layered reduced graphene oxide aerogel, comprising the following steps:
[0080] (1) Preparation of pre-reduced graphene oxide gel
[0081] First, a certain amount of graphene oxide powder was weighed and dissolved in deionized water at a concentration of 5 mg / ml. Then, a certain amount of ascorbic acid was added to the graphene oxide solution, and the mass of ascorbic acid was twice the mass of graphene oxide. The mixed solution was ultrasonically dispersed for 30 minutes, stirred for 2 hours, poured into a plastic mold with a wedge-shaped block of polydimethylsiloxane (PDMS) (wedge angle of 20°), and reduced at 60°C for 120 minutes to transform it from a sol state to a microgel state.
[0082] (2) Preparation of layered reduced graphene oxide aerogel
[0083] The mold was placed on a copper block that had been immersed in liquid nitrogen in advance. After being completely frozen, it was placed in a pre-frozen freeze dryer and dried for 72 hours at -60°C and 5 Pa. In order to remove impurities and enhance chemical cross-linking, the dried aerogel was heat treated at 800°C for 2 hours to obtain a layered structured reduced graphene oxide aerogel.
[0084] Unlike Examples 1 and 2, Example 3 is a precursor of layered silicon carbide aerogel, which helps to provide a novel preparation strategy for layered reduced graphene oxide aerogel, which only requires one reducing agent, takes less time, and has lower cost. The microscopic morphology and optical image of the precursor of silicon carbide aerogel prepared in this example are shown in Figure 2 and Figure 3, respectively. Fig.10 and Fig.11 As shown in the figure, it can be seen that the reduced graphene oxide aerogel is black in appearance and its microscopic morphology shows a significant layered structure.
[0085] Comparative Example 1
[0086] This comparative example provides a method for preparing reduced graphene oxide aerogel, comprising the following steps:
[0087] (1) Preparation of pre-reduced graphene oxide gel
[0088] First, a certain amount of graphene oxide powder was weighed and dissolved in deionized water at a concentration of 5 mg / ml; then, a certain amount of ascorbic acid was added to the graphene oxide solution, and the mass of ascorbic acid was twice the mass of graphene oxide. The mixed solution was ultrasonically dispersed for 30 minutes, stirred for 2 hours, and then poured into a plastic mold with a polydimethylsiloxane (PDMS) wedge (wedge angles were 0, 5, 10, and 15 degrees, respectively), and reduced at 60°C for 120 minutes to transform it from a sol state to a microgel state.
[0089] (2) Preparation of layered reduced graphene oxide aerogel
[0090] The mold was placed on a copper block that had been immersed in liquid nitrogen in advance. After being completely frozen, it was placed in a pre-frozen freeze dryer and dried for 72 hours at -60°C and 5 Pa. In order to remove impurities and enhance chemical cross-linking, the dried aerogel was heat treated at 800°C for 2 hours to obtain reduced graphene oxide aerogel.
[0091] In this comparative example, the reduced graphene oxide aerogel is prepared by adjusting the wedge angle (0°, 5°, 10°, 15°, 20°). The schematic diagram of the freezing method (bidirectional) with a wedge angle is shown in FIG. Fig.13 The results show that: at 0°, 5°, 10°, and 15°, a good layered structure cannot be formed. Taking the wedge angle of 10° as an example, its microstructure is as follows Fig.12 As shown, the layered structure can only be achieved with a wedge angle of 20° (see Fig.10 ).
[0092] In addition, when the wedge angle is greater than 20°, the mold volume requirement is high and the consumption of raw materials is higher. Therefore, when the wedge angle is 20°, a layered structure can be achieved while ensuring a lower preparation cost.
[0093] Comparative Example 2
[0094] This comparative example provides a method for preparing a layered silicon carbide aerogel, comprising the following steps:
[0095] (1) Preparation of pre-reduced graphene oxide gel
[0096] First, a certain amount of graphene oxide powder was weighed and dissolved in deionized water at a concentration of 10 mg / ml; then, a certain amount of ascorbic acid was added to the graphene oxide solution, and the mass of ascorbic acid was twice the mass of graphene oxide. The mixed solution was ultrasonically dispersed for 30 minutes, stirred for 2 hours, and then poured into a plastic mold with a polydimethylsiloxane (PDMS) wedge (wedge angle of 20°) block, and pre-reduced at 60°C for 100 minutes to transform it from a sol state to a microgel state.
[0097] (2) Preparation of reduced graphene oxide aerogel
[0098] The mold was placed on a copper block that had been immersed in liquid nitrogen in advance. After being completely frozen, it was placed in a pre-frozen freeze dryer and dried for 72 hours at -60°C and 5 Pa. In order to remove impurities and enhance chemical cross-linking, the dried aerogel was heat treated at 800°C for 2 hours to obtain reduced graphene oxide aerogel.
[0099] (3) Preparation of layered silicon carbide aerogel by gas phase siliconization
[0100] The above-mentioned aerogel is used as a carbon source, silicon powder is used as a silicon source, and the mass ratio of reduced graphene oxide aerogel to silicon powder and silicon dioxide powder is 1: (6-8). The carbon source is placed on the silicon source, and they are placed together in a crucible and placed in a tubular furnace. After evacuation, argon gas is filled as a protective atmosphere, and the temperature is heated to 1550°C according to the gradient heating method (the heating rate is fast at first and then slow, from 5°C / min to 1.5°C / min) for high-temperature gas phase siliconization, and the heat preservation time is 2h.
[0101] Different from Examples 1 and 2, Comparative Example 2 adopts a method of changing the silicon source, using silicon powder as the single silicon source for high-temperature vapor phase siliconization. The microscopic morphology is shown in FIG. Fig.14 As can be seen from the figure, the silicon carbide aerogel obtained by vapor phase siliconization of silicon powder is a layered structure, which is similar to Figure 3 and Figure 8 A comparison shows that it does not have a nanowire filling structure and a nanowire structure.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a lightweight, high temperature resistant silicon carbide aerogel, characterized in that: The steps include: S1, mixing and dispersing graphene oxide powder, ascorbic acid and deionized water, and then pre-reducing them to obtain pre-reduced graphene oxide gel; Specifically, step S1 includes: S11, dissolving graphene oxide powder in deionized water to obtain a graphene oxide solution; the concentration of the graphene oxide solution is 5 to 20 mg / ml; S12, adding ascorbic acid to the graphene oxide solution, performing ultrasonic dispersion and stirring to obtain a mixed solution; the mass ratio of the graphene oxide powder to the ascorbic acid is 1:2; S13, pouring the mixed solution into a mold, placing the mold in an oven at 60-70° C. for 1-2 hours for pre-reduction, and obtaining a pre-reduced graphene oxide gel; S2, freezing the pre-reduced graphene oxide gel, and then freeze-drying and high-temperature thermal reduction after the pre-reduced graphene oxide gel is completely frozen to obtain a layered reduced graphene oxide aerogel; Specifically, step S2 includes: S21, after the pre-reduction is completed, the mold is placed on a copper block that has been immersed in liquid nitrogen in advance until it is completely frozen; the bottom of the mold has a polydimethylsiloxane wedge block, and the wedge angle of the wedge block is not less than 20°; S22, after being completely frozen, the mold is placed in a pre-frozen freeze dryer for drying, with the temperature controlled at -50°C to -70°C and the pressure at 3-10Pa; S23, subjecting the dried aerogel to high-temperature thermal reduction at 700-900° C. to obtain layered reduced graphene oxide aerogel; S3, using a mixed powder of silicon powder and silicon dioxide powder as a silicon source, mixing it with a layered reduced graphene oxide aerogel, and performing high-temperature gas phase siliconization to obtain a nanowire-filled layered silicon carbide aerogel; Specifically, step S3 includes: S31, fully mixing silicon powder and silicon dioxide powder, and placing the obtained mixed powder as a silicon source at the bottom of a crucible; S32, placing a layered reduced graphene oxide aerogel on the mixed powder; the mass ratio of the layered reduced graphene oxide aerogel, silicon powder and silicon dioxide powder is 1:(3-4):(9-10); S33, placing the crucible in a tubular furnace, heating it to 1500-1600° C. in an inert gas atmosphere for high-temperature gas phase siliconization to obtain nanowire-filled layered silicon carbide aerogel.
2. A lightweight, high temperature resistant silicon carbide aerogel, characterized in that: The method according to claim 1 is used to prepare the product.
3. Application of the lightweight, high temperature resistant silicon carbide aerogel according to claim 2 in the manufacture of aircraft, ships and steam turbines.
Citation Information
Patent Citations
Three-dimensional multistage structure nano silicon carbide, preparation method and application thereof
CN108285145A
Graphene oxide aerogel, reduced graphene oxide aerogel as well as preparation methods and applications of graphene oxide aerogel and reduced graphene oxide aerogel
CN109096526A
Long-range ordered separation membrane as well as preparation method and application thereof
CN117398854A